Medical rehabilitation of patients with menopausal syndrome and surgical menopause: contribution of magnesium deficiency correction - D. V. Blinov; А. G. Solopova; Е. Е. Achkasov; G. К. Bykovshchenko; D. А. Petrenko (Фармакоэкономика)
Background. The increase in the proportion of patients with menopausal syndrome (MS) and surgical menopause, including women in the recovery phase after radical surgical treatment of the reproductive system cancer, is a characteristic trend of the 21st century. Part of them receive menopausal hormone therapy (MHT). This determines the relevance of the analysis of the specified cohort of patients to enhance rehabilitation programs designed to improve the quality of life (QoL) in this category of gynecological patients.Objective: subanalysis of primary data from the MAGYN study cohort of MHT treated women with MS and surgical menopause.Material and methods. The MAGYN observational non-interventional study of the real clinical practice included 9168 women, of whom 1528 represented a group of previously not characterized MHT treated women with MS and surgical menopause. To determine the number of patients with magnesium deficiency (MD), a Magnesium Deficiency Questionnaire (MDQ) was used, a biochemical blood test with an indicator of serum magnesium concentration was evaluated. The profile of the participants was analyzed by the presence of general somatic pathologies, obstetric, gynecological history, complaints, symptoms of MD on a visual-analog scale. The QoL was assessed with the help of The World Health Organization Quality of Life Brief Version (WHOQOL-BREF) before the start of a 4-week course of MD supplementation and after treatment.Results. According to the MDQ results, the prevalence of DM was 79.4%, which exceeded the results of all other groups in the study. Women with MD had a higher incidence of viral infections (19.2% vs. 22.7%; p=0.028), vegetative-vascular dystonia (26.2% vs. 29.7%; p=0.0466) and osteochondrosis (42.9% vs. 46.8%; p=0.0453). A subgroup of participants with verified MD demonstrated significantly more pronounced symptoms, such as irritability (4.9±3.5 vs. 4.6±3.4 points in the general group; p=0.0437), sleep disorders (4.4±2.3 vs. 4.2±2.3 points; p=0.0491), back pain (3.9±2.0 vs. 3.7±2.0; p=0.0405), and increased fatigue (4.6±2.3 vs. 4.4±2.3 points; p=0.0444). After the end of the course of therapy with fixed dose combination of magnesium citrate and pyridoxine, the sum of MDQ scores decreased from 46.0±12.7 to 29.2±15.1 points (p<0.001) in combination with an increase in the plasma concentration of magnesium to 0.79±0.23 mmol/l; women's satisfaction with their physical, psychological, social well-being increased (from 21.1±4.5 to 26.2±3.5 points; from 24.8±4.9 to 28.1±4.4 points, and from 9.3±2.7 to 11.0±2.8 points, respectively; p<0.001); self-perception increased from 18.2±3.7 to 22.2±3.6 points. Thus, there was a significant decrease in the severity of MD and a significant improvement in QoL according to WHOQOL-BREF, which is important in the rehabilitation of such patients.Conclusion. The profile of patients with MS and surgical menopause receiving MHT, including the period of recovery after radical surgical treatment of reproductive cancer, is characterized by MD and decreased QoL. It seems effective to introduce MD correction into the complex rehabilitation program of such patients. It is necessary to conduct further studies to improve the rehabilitation measures in this cohort of patients.